2021
DOI: 10.1007/s11604-021-01197-3
|View full text |Cite
|
Sign up to set email alerts
|

Amide proton transfer imaging in differentiation of type II and type I endometrial carcinoma: a pilot study

Abstract: Purpose This study aimed at evaluating the efficacy of amide proton transfer (APT) imaging in differentiation of type II and type I uterine endometrial carcinoma. Materials and methods Thirty-three patients diagnosed with uterine endometrial carcinoma, including 24 with type I and 9 with type II carcinomas, underwent APT imaging. Two readers evaluated the magnetization transfer ratio at 3.5 ppm [MTRasym (3.5 ppm)] in each type of carcinoma. The average MTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Amide proton transfer‐weighted (APTw) imaging is a magnetic resonance molecular‐imaging technique based on the chemical exchange saturation transfer phenomenon, 15 and it has been applied to the diagnosis of EC, together with the pathological features and immunohistochemical indicators (Ki‐67). Ochiai et al 16 reported that the APT value of type II EC was higher than that of type I EC. Takayama et al 17 found that the APT value was positively correlated with the histological grade of endometrioid adenocarcinoma.…”
mentioning
confidence: 97%
“…Amide proton transfer‐weighted (APTw) imaging is a magnetic resonance molecular‐imaging technique based on the chemical exchange saturation transfer phenomenon, 15 and it has been applied to the diagnosis of EC, together with the pathological features and immunohistochemical indicators (Ki‐67). Ochiai et al 16 reported that the APT value of type II EC was higher than that of type I EC. Takayama et al 17 found that the APT value was positively correlated with the histological grade of endometrioid adenocarcinoma.…”
mentioning
confidence: 97%
“…A total of five groups have contributed reports that were involving cervical cancer and endometrial carcinomas along with healthy uterine tissues. APT values changed with cancer type [ 56 ], histology grade [ 60 ], proliferation, as well as menstrual cycle. The APT method was co-studied with other fMRI methods [ 57 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Ochiai et al [ 56 ] evaluated the efficacy of APT imaging in the differentiation of type I and type II uterine endometrial carcinoma in a 33-patient study. Results show that APT imaging has the potential to determine the type of endometrial cancer.…”
Section: Applicationsmentioning
confidence: 99%
“…Previous data suggested that, due to over-expressed mobile protein and peptide concentrations, APTw can assess the pathological grade of malignant tissue. For example, a previous study found that histologically type II, high-grade, high International Federation of Gynecology and Obstetrics (FIGO) stage and lymphovascular space invasion (LVSI)-positive EC have higher APT values (14,15). In addition, Li et al (16) showed that the APT value was moderately positively correlated with the expression index of the nuclear antigen Ki-67 associated with EC cell proliferation.…”
Section: Introductionmentioning
confidence: 99%